ONLINE TEACHING-LEARNING PROCESSES: POSSIBILITIES TO THINK EDUCATIONS IN/WITH CYBERCULTURE - Dilton Ribeiro Couto Junior (Travessias, 2014)
This article presents part of the results of a recently concluded Masters Degree research. The objective of this work is to think educations in/with cyberculture, seeking new possibilities so students and teachers learn together with the use of digital interfaces in communication processes. Therefore, the research investigated the relations that ninety-eight youths, among them newly qualified teachers, established with their equals on the Facebook interface. The theoretical-methodological background is based on the contribution of the virtual ethnography and the dialogue with authors of the communication and education fields. The conclusions of the research aim at the relevance of Facebook to provide that the different voices of teachers and students are heard and interpellated, creating narrower bonds between everyone involved on the learning and teaching processes, and opening new possibilities as the online dialogue is intensified among the internet users. This provided ways to rethink the pedagogical practices in the context of the dynamic communications, considering the interaction and collaboration, proper of cyberculture.